Prescribing with precision: fluids, food and furosemide - Rand Al-Assadi; Huda Mahmoud; Rebecca Jackson; Holly Trippe (Clinical Medicine)
Introduction: Fluid prescription is a critical aspect of patient care, especially among inpatients aged over 65 years, who are more susceptible to fluid and electrolyte imbalances because of ageing and comorbidities.1 Studies show significant patient harm from inappropriate fluid management, with National Institute of Health and Care Excellence (NICE) reporting that one in five patients receiving intravenous (IV) fluids suffer complications, including pulmonary oedema in 67–89%.2 The West Midlands Better Training Better Care pilot demonstrated that 47% of resident doctors would prescribe 3 L/24 h maintenance fluids for a 70-kg patient, exceeding NICE recommendations of 2.1 L3 and 22% of patients made nil by mouth (NBM) remained without oral intake for >72 h without reassessment plans.4 This study examined fluid, nutrition and diuretic-prescribing practices within older medical patients. Methods: This retrospective study examined electronic and paper records of individuals over 65 years admitted to medical wards. Data collected included patient demographics, weight documentation, rationale for NBM status or maintenance fluids, prescribed fluid volumes and types, electrolyte abnormalities and corrections, and renal function (including community and/or hospital-acquired acute kidney injury). Accuracy of fluid balance documentation and NBM resolution processes were assessed. Results: Preliminary data included 25 patients, 79.02±8.78 years, with 36% (n=9) made NBM for a median 3 (1.7–5) days. Unsurprisingly, individuals who were NBM had significantly more fluid prescribed (8±5.53 L) vs non-NBM (5.45±1.76 L; p=0.0072) (Table 1). There was a positive correlation between individuals who had higher IV fluid administration and longer lengths of stay (LOS) (r=0.5395, p=0.0100). Interestingly, it was demonstrated that individuals on NBM had longer LOS (16.11±15.02 days) vs non-NBM (11.27±9.12; p=0.5), although this was not statistically significant. Of the 10 patients who were NBM, only one (10%) received speech and language therapy (SALT) assessment with an alternative feeding plan implemented. The remaining patients either had their NBM status resolved before SALT review or, in one case, died while awaiting assessment.Average admission weight was 68.59±20.23 kg, with final discharge weight increasing to 70.52±22.19 kg (p=0.04). Weight documentation was notably deficient, with 52% of patients having no final weight recorded. Those who had follow-up weights documented gained on average 3.2±4.74 kg. Concerning medication management, only 53% of patients had diuretics appropriately held during periods of NBM or maintenance fluid therapy, potentially compounding fluid balance challenges. Conclusion: Preliminary findings reveal substantial gaps in fluid management practices for older patients, including excessive fluid administration and inappropriate diuretic continuation. Delayed SALT assessments and unnecessary NBM status led to significant periods without oral nutrition. Documentation was lacking, with ∼25% of patients receiving maintenance fluids without documented reasoning and half without follow-up weights.Educating resident doctors on fluid prescribing and bedside swallowing assessments is essential to reduce prolonged NBM periods and decrease SALT burden. Ongoing analysis will inform targeted educational interventions, poster guidelines, and potential policy revisions, aiming to improve fluid prescription and streamlined NBM management protocols.